Формалізація стратегій хмарної міграції інформаційних систем - Євланов, М. В.; Шутько, В. В. (ТОВ «Видавництво Ліра-К», 2025)
This work is devoted to information systems cloud migration strategies formalization. The formalized representation of the cloud migration strategies allows automating the process of selection of the most suitable migration strategy that meets business requirements by providing a unified strategies view with their corresponding qualitative and quantitative metrics.
Keywords: хмарна міграція; міграція